A NEW SPECIES OF CRYPTONEMIA FROM BRAZIL - Pinheiro Joventino, Francisca; de Oliveira Filho, Eurico Cabral (Arquivos de Ciências do Mar, 2018)
The opportunity to examine a collection of depth plants from some places on the Brazilian littoral brought us in contact with a very interesting species of Cryptonemia that we suppose to be a new one. Though poorly known, the Brazilian sublittoral seems to have a very rich and diversified flora promising to be a good source of interesting and unknown material.